2019
DOI: 10.15446/rsap.v21n1.77725
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of an adult population sample in Barranquilla, Colombia

Abstract: Objective The aim of this study was to estimate values of health-related quality of life (HRQOL) by focusing on the physical and mental health of an adult population sample in the city of Barranquilla, Colombia.Materials and Methods Cross-sectional study with 368 adults representing an adult population. The questionnaires included the health-related quality of life “CDC-Healthy Days”, the Zung Self-Rating Depression Scale, and the Overall Disability Sum Score. The prevalence of fair or poor health status (FPH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Previous studies observed that polypharmacy was strongly associated with a poorer QoL among PLWHIV [21][22][23]. Furthermore, Keaei et al [24], showed that the dimensions of pain/discomfort and anxiety/depression were more affected in this kind of patients coinciding with the results of our study. However, the definition of polypharmacy employed by Keaei et al could be inappropriate to relate the QoL since we can find patients who take the same number of drugs but have different MRCI values.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies observed that polypharmacy was strongly associated with a poorer QoL among PLWHIV [21][22][23]. Furthermore, Keaei et al [24], showed that the dimensions of pain/discomfort and anxiety/depression were more affected in this kind of patients coinciding with the results of our study. However, the definition of polypharmacy employed by Keaei et al could be inappropriate to relate the QoL since we can find patients who take the same number of drugs but have different MRCI values.…”
Section: Resultssupporting
confidence: 91%